THE EFFECT OF PERCEIVED TRUST AND PERCEIVED ENJOYMENT ON REPURCHASE INTENTION: (Study on Tokopedia Users in Medan City) - Mulia, Nana Tri; Adlina, Hafiza (Transpublika Publisher, 2024)
One of the e-commerce that has been well known by some Indonesians is Tokopedia. Tokopedia is ranked as the first most trusted e-commerce and as the most visited e-commerce in 2022. The domination of using Tokopedia compared to other e-commerce has led to various perceptions provided by Tokopedia so that it attracts users to repurchase. The purpose of this study was to determine the effect of perceived trust and perceived enjoyment on repurchase intention of Tokopedia users in Medan City. This research was conducted using quantitative techniques with a research sample of 100 respondents who are Tokopedia users in Medan City. The analysis techniques used include instrument tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study show that Perceived Trust has a significant positive effect on Repurchase Intention with a sig value of 0.000 <0.05 and Perceived Enjoyment has a significant positive effect on Repurchase Intention with a sig value of 0.019 <0.05. In simultaneous testing, the Perceived Trust and Perceived Enjoyment variables simultaneously have a positive effect on Repurchase Intention with an influence level of 61.3%.